Study on compaction control standard of different contact clay areas for 300m high core rockfill dam. Issue 7 (October 2021) - Jin, W; Shao, L; Yu, T; Zhu, X W; Jiang, Y Y; Yang, L Y
Abstract: Based on several 300m high core rockfill dam in Southwest China, through studying the stress distribution, shear deformation and stress level of different gravel soil core walls, combined with the mechanical test results of contact clay under different compactness and moisture content, the compactness control standards for different contact clay areas of high core rockfill dam are proposed. The results show that for the contact clay area of dam slope on both banks, for the area where the stress level exceeds 0.9, the compaction degree should be increased, so as to improve the shear strength of the soil in the area; for the area with large shear deformation, the compaction degree should be reduced, so as to adapt to the larger shear deformation with larger allowable shear strain. During the filling of contact clay, the water content should not be too low or too high, and should be controlled in an interval near the optimal water content. Taking the test soil materials of the project as an example, it is suggested that the lower limit of filling water content should be controlled at 1% of the optimal water content, and the upper limit should be controlled at 3.5% of the optimal water content.